2018
DOI: 10.1080/15384101.2018.1526599
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA 101368/miR-200a axis modulates the migration of hepatocellular carcinoma through HMGB1/RAGE signaling

Abstract: Hepatocellular carcinoma (HCC), one of the most common type of cancers, is highly refractory to most systemic therapies. Understanding the genomic dysregulations, in particularly non-coding RNA (ncRNA) dysregulations, in HCC may provide novel strategies to HCC treatment. In our previous study, we demonstrated the key role of miR-200a-mediated HMGB1/RAGE signaling in HCC carcinogenesis. In the present study, we identified circular RNA (circRNA)-miRNA pair that might modulate the migration of HCC cell lines base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 20 publications
(27 reference statements)
1
41
0
1
Order By: Relevance
“…Moreover, expression of RAGE itself is also closely associated with the invasiveness and metastatic activities of gastric cancer 6 . Additionally, microRNA is reported to participate in RAGE-ligands mediated migration or cancer progression [46][47][48] . In this study, RAGE was overexpressed to hoist RAGE-mediated signaling and to investigate the effect of RAGE axis on the tumorigenesis of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, expression of RAGE itself is also closely associated with the invasiveness and metastatic activities of gastric cancer 6 . Additionally, microRNA is reported to participate in RAGE-ligands mediated migration or cancer progression [46][47][48] . In this study, RAGE was overexpressed to hoist RAGE-mediated signaling and to investigate the effect of RAGE axis on the tumorigenesis of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, miR-200a-3p and miR-141-3p are downregulated in the plasma samples of patients with endometriosis compared with that in healthy controls, suggesting that these miRNAs could be used as putative noninvasive diagnostic biomarkers of endometriosis 38 . Li et al 39 found that inhibition of miR-200a could promote migration and high mobility group box 1 expression, while decreasing E-cadherin expression in HCC cell lines. Another study showed that EMT progression was inhibited in miR-200a-3p -overexpressing papillary thyroid cancer (PTC) cells 40 .…”
Section: Discussionmentioning
confidence: 99%
“…However, currently there are no effective biomarkers for the early diagnosis of HCC, and the molecular mechanisms underlying HCC metastasis remains unclear. 35,36 EPDR1, a member of piscine brain glycoproteins, plays a role in cell adhesion. To gain detailed insights into the potential functions of EPDR1 and its regulatory network in HCC, we performed bioinformatics analysis using publicly available data, which we hope will benefit future research related to HCC.…”
Section: Discussionmentioning
confidence: 99%